1997
DOI: 10.1002/(sici)1096-8628(19970725)74:4<398::aid-ajmg11>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Personality and language characteristics in parents from multiple-incidence autism families

Abstract: Several studies have suggested that the genetic liability for autism may be expressed in non-autistic relatives of autistic probands, in behavioral characteristics that are milder but qualitatively similar to the defining features of autism. We employ a variety of direct assessment approaches to examine both personality and language in parents ascertained through having two autistic children (multiple-incidence autism parents) and parents of Down syndrome probands. Multiple-incidence autism parents had higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(138 citation statements)
references
References 35 publications
(42 reference statements)
3
130
1
1
Order By: Relevance
“…[57][58][59][60] In the ICD-10 classification for schizophrenia and related disorders, 7 some of the diagnostic criteria appear to be very close to the criteria for AS. This seems to be valid especially for schizoid personality disorder.…”
Section: Discussionmentioning
confidence: 99%
“…[57][58][59][60] In the ICD-10 classification for schizophrenia and related disorders, 7 some of the diagnostic criteria appear to be very close to the criteria for AS. This seems to be valid especially for schizoid personality disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Within these families, there are also elevated rates of social difficulties; higher incidences of cognitive, communication, learning and executive function deficits; increased stereotyped behaviors; and anxiety, affective, language, and pragmatic disorders. 33,[49][50][51][52][53][54][55] Monozygotic twin pair studies have also shown a high concordance rate (60%) for DSM-IV Autistic Disorder, 71% for the broader autistic spectrum phenotype, and 92% for an even broader phenotype of social and communication deficits with stereotyped behaviors that nonetheless were clearly differentiated from normal. In contrast, no concordance for autism was noted in dizygotic twin pairs and only 10% were concordant for some form of cognitive, social or language deficit.…”
Section: Neurology 2000;55:468-479mentioning
confidence: 99%
“…Parents of autistic children perform in the superior range on the Embedded Figures Test [20], visual search tasks [163], and other tasks that require processing of parts and details [102], but are below normal performance at inferring mental state from facial expression [20], a task that demands configural and integrative processing. In addition, parents share difficulties in pragmatic language tasks [87], impairments in some tasks that tap executive function [114], and autistic personality characteristics such as rigidity, aloofness, and anxiety [179,178]. Many first-degree relatives show a disparity between performance IQ and verbal IQ, with the performance score being lower [89,177,87] due to impairment on Picture Arrangement and Picture Completion, both of which demand attention to global, contextual information.…”
Section: Phenotypes Within and Beyond The Diagnosismentioning
confidence: 99%